A method for evaluating the coating effect of coated modified filler powder for thermal interface

By conducting multi-directional fine testing of the coated modified filler powder for thermal interfaces, an evaluation method is established, and the problem of inability to accurately predict the coating effect in the prior art is solved, and rapid and economical performance prediction is achieved.

CN115932114BActive Publication Date: 2025-04-08JONES TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310001500.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-03
Publication Date
2025-04-08
Estimated Expiration
2043-01-03

AI Technical Summary

Technical Problem

The prior art lacks effective and accurate methods to evaluate the coating effect of thermal interface coating modified filler powder, resulting in the inability to accurately predict its performance in the final product formulation.

Method used

By conducting multi-directional collaborative fine-grafting test and characterization of coated modified filler powders with thermal interfaces, including testing the coating residue, effective graft density, specific surface area change rate, particle size change rate and surface energy, an evaluation method for coating effect was established.

Benefits of technology

Accurate and effective evaluation of coated modified filler powder is achieved, and its performance in the formula can be predicted without formula verification, short test cycle and low raw material consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The present invention provides a method for evaluating the coating effect of a coated modified filler powder for a thermal interface, comprising the following steps: analyzing and characterizing the coated modified filler powder for a thermal interface; the coated modified filler powder is prepared by coating and modifying filler powder with a coating agent; the analysis and characterization comprises: item (1): testing the coating agent residual rate of the coated modified filler powder; item (2): testing the effective grafting density of the coated modified filler powder; item (3): testing the specific surface area change rate of the filler powder before and after coating; item (4): testing the particle size change rate of the filler powder before and after coating; item (5): testing the surface energy of the coated modified filler powder; the above test items (1) to (5) are not restricted in order. The evaluation method of the present invention establishes a corresponding relationship between the microstructure of the coated powder and the performance effect, and can accurately and effectively predict the quality of the surface coating modification effect of the filler powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material analysis, and in particular to a method for evaluating the coating effect of a coated modified filler powder for a thermal interface. Background Art

[0002] As a supporting industry of the information industry, semiconductor technology is facing a major bottleneck and challenge - thermal wall. In other words, high-speed and high-density micro / nanoelectronic devices generate huge amounts of heat in a small space. This heat accumulates in a very small range, causing the temperature of the electronic devices to rise sharply. In this case, the reliability and speed of the electronic device operation are reduced, and eventually the integrated circuit is burned. Therefore, how to dissipate the generated heat in a timely manner is an important issue facing the development of the semiconductor electronics industry.

[0003] From a microscopic point of view, at the interface formed by different materials, the roughness of the solid surface will fill the interface with air, so that the actual contact area is much smaller than the surface area of ​​the interface. Since the thermal conductivity of air is very poor, it will greatly increase the overall thermal resistance of the interface. In order to reduce the impact of this unfavorable factor, people usually fill the interface with thermal interface materials (TIM) with high thermal conductivity. This type of material needs to have a certain degree of deformability and fluidity, so as to fill the gaps at the interface as much as possible and increase the contact area. The more common thermal interface materials are thermal grease, thermal gel, thermal conductive adhesive, thermal pad, phase change material, etc. They are all composite materials that add thermal conductive fillers (such as zinc oxide, aluminum oxide, etc.) to polysiloxane polymer substrates or carbon chain hydrocarbon oils. This type of filled TIM material is usually a high-filling system with a volume filling rate of >70%, and the interface layer between the filler and the base glue accounts for a large proportion, so the interface layer structure will play an important role in performance. The interface between the composite material filler and the matrix can be improved by surface coating modification of thermal conductive filler powder, so coating modification technology has been continuously studied in the industry. The structure of the coating layer directly affects the effect of powder coating, and how to accurately evaluate and characterize the microscopic interface structure of the powder coating layer has become the key to powder coating modification technology.

[0004] At present, the existing evaluation methods for the effect of thermal conductive filler coating in the industry are mostly focused on the comprehensive verification of formula performance, such as the characterization of thermal conductivity, fluidity, stability, etc. These are all indirect methods for characterizing the coating effect of powders. Such evaluation methods not only have a long test cycle, but also high raw material consumption. At the same time, the industry lacks effective and accurate evaluation methods for testing the coated modified filler powder itself to predict the effect after mixing it into the formula. The existing prediction methods include surface wettability, activation index, oil absorption value, dispersibility viscosity method (testing the viscosity in the formula), etc., but these evaluation methods are low in accuracy and effectiveness. They are rough evaluation methods. For example, different samples have similar or basically the same oil absorption value, activation index, viscosity and other characteristics, but in actual use, some samples can pass the test while others cannot, so it is impossible to accurately and effectively evaluate the effect of powder coating modification. Therefore, most of the current scientific research and production methods adopt the method of directly mixing the coated modified filler powder into the final product formula for actual application, and then evaluating the coating modification effect based on the actual application effect, but lack effective and accurate evaluation methods for testing the coated modified filler powder itself to predict the effect after mixing into the formula. The reason is that the existing powder testing technology is not precise, complete, and comprehensive in testing the effect of the modified treatment of the powder filler surface after coating, which makes it impossible to correspond to the actual formula performance after the coated modified powder is mixed into the product formula, and thus it is impossible to effectively and accurately pre-evaluate the effect of the powder after coating and modification. Summary of the invention

[0005] In view of this, the present invention provides an evaluation method for the coating effect of coated filler powder for thermal interface. The evaluation method provided by the present invention establishes a corresponding relationship between the microstructure of the coated powder and the performance effect, and can accurately and effectively predict the quality of the surface coating modification effect of the filler powder.

[0006] The present invention provides a method for evaluating the coating effect of a coated modified filler powder for a thermal interface, comprising the following steps:

[0007] Analyze and characterize the coated modified filler powder for thermal interface;

[0008] The coated modified filler powder is obtained by coating and modifying the filler powder with a coating agent;

[0009] The analytical characterization includes:

[0010] Project (1): Test the residual rate of coating agent for coated modified filler powder;

[0011] Project (2): Test the effective grafting density of coated modified filler powder;

[0012] Project (3): Test the change rate of specific surface area of ​​filler powder before and after coating;

[0013] Project (4): Test the particle size change rate of filler powder before and after coating;

[0014] Project (5): Testing the surface energy of coated modified filler powder;

[0015] There is no order restriction for the above test items (1) to (5).

[0016] Preferably,

[0017] Project (1): Test the residual rate of coating agent for coated modified filler powder, including:

[0018] The GC-MS test method and the external standard method are used to quantitatively analyze the coated modified filler powder sample, thereby obtaining the coating agent residual rate in the coated modified filler powder sample;

[0019] Project (2): Test the effective grafting density of coated modified filler powder, including:

[0020] The total weight loss of the coated modified filler powder in the temperature range of 250-800°C was measured and calculated by the TGA test method, and then the effective grafting density GD of the coated modified filler powder was calculated by the following formula:

[0021]

[0022] in,

[0023] GD: effective grafting density of coated modified filler powder, unit: mmol / g;

[0024] M w : Molecular mass of the coating agent, unit: g / mol;

[0025] △m: total weight loss of coated modified filler powder in the temperature range of 250-800℃, unit: %;

[0026] 1-△m: mass fraction of powder before coating to total powder after coating, unit: %;

[0027] Project (3): Test the change rate of specific surface area of ​​filler powder before and after coating, including:

[0028] The specific surface area SA of the filler powder before coating was tested by static volumetric method. b and the specific surface area SA of the coated modified filler powder obtained after coating a , and then calculate the specific surface area change rate SARC before and after the filler powder is coated according to the following formula:

[0029]

[0030] in,

[0031] SARC: the specific surface area change rate of filler powder before and after coating, unit: %;

[0032] SA b : Specific surface area of ​​filler powder before coating, unit: m 2 / g;

[0033] SA a : Specific surface area of ​​the coated modified filler powder obtained after coating, unit: m 2 / g;

[0034] Project (4): Test the particle size change rate of filler powder before and after coating, including:

[0035] The median diameter D of the filler powder before coating was measured using the LPSD test method. 50b The median diameter D of the coated modified filler powder obtained after coating 50a ; Then calculate the median diameter change rate RD before and after powder coating according to the following formula: 50 :

[0036]

[0037] in,

[0038] RD 50 : Median diameter D before and after powder coating 50 Rate of change, unit: %;

[0039] D 50b : Median diameter D of filler powder before coating 50 ;

[0040] D 50a : The median diameter D of the coated modified filler powder obtained after coating 50 ;

[0041] Item (5): Testing the surface energy of coated modified filler powder, specifically including: testing and calculating the surface energy of coated filler powder according to Wu S method.

[0042] Preferably, item (1) specifically includes: S1, establishing an external standard curve; S2, performing GC-MS test on the coated modified filler powder sample test solution to obtain the GC-MS test value of the coated modified filler powder sample test solution; S3, matching the GC-MS test value of the coated modified filler powder sample test solution with the external standard curve to obtain the coating agent content in the coated modified filler powder sample.

[0043] Preferably, in item (2), the test conditions of the TGA test method are: nitrogen atmosphere, gas flow rate 15-60 mL / min, and heating rate from room temperature to 800° C. at 3-5° C. / min.

[0044] Preferably, in item (3), the filler powder before coating and the coated modified filler powder obtained after coating are pretreated before the specific surface area test;

[0045] The pretreatment is heat treatment; the temperature of the pretreatment is 120-200° C. and the time is 1-2 hours.

[0046] Preferably, in item (4), the process of testing the particle size using the LPSD test method specifically includes: K1, dispersing the powder sample in a dispersion medium to obtain a dispersion; K2, transferring the dispersion into an LPSD analyzer, setting the test level, and performing a particle size test.

[0047] Preferably, item (4) further includes: testing and calculating the maximum particle size change rate RD of the powder before and after coating 100 ;

[0048] The test calculates the maximum particle size change rate RD before and after the powder is coated 100 The process includes: using the LPSD test method to test the maximum particle size D of the filler powder before coating 100b The maximum particle size D of the coated filler powder obtained after coating 100a ; Then calculate the maximum particle size change rate RD before and after powder coating according to the following formula: 100 :

[0049]

[0050] in,

[0051] RD 100 : Maximum particle size D before and after powder coating 100 Rate of change, unit: %;

[0052] D 100b : Maximum particle size D of filler powder before coating 100 ;

[0053] D 100a : The maximum particle size D of the coated modified filler powder obtained after coating 100 .

[0054] Preferably, item (5) specifically includes:

[0055] H1. Test the contact angle of coated modified filler powder;

[0056] H2, the surface energy of the coated modified filler powder is calculated by the calculation equation of Wu S method;

[0057] The calculation equation of the Wu S method is as follows:

[0058]

[0059] Where θ is the wetting contact angle between liquid and solid; γ lg is the liquid-gas interfacial tension; γ sg is the solid-gas interfacial tension; d is the dispersion force component in the interfacial tension, and p is the polar force component in the interfacial tension; the above equation contains two variables, and it is necessary to test the contact angle of the same solid interface twice with different liquids, and solve the simultaneous equations to obtain the dispersion force and polar force of the solid-gas interface, thereby obtaining the surface free energy of the solid; in the process of the two contact angle tests, the titrants selected were water and diiodomethane respectively.

[0060] Preferably, item (6) is also tested: analyzing the pre-reaction degree of the coating agent;

[0061] The pre-reaction degree of the coating agent is analyzed by a GC-MS test method; specifically, the coating agent is mixed with an alcohol aqueous solution to obtain a mixed solution A, and the mass percentage content W0 of the coating agent in the mixed solution A is recorded; the mixed solution A is stirred to react, and when the reaction reaches a certain degree, a reaction solution B is obtained; the reaction solution B is weighed and fixed to a certain volume with a constant volume reagent; then, ultrasonic extraction, immersion extraction, stirring extraction or high-temperature boiling are performed; then, drying is performed to obtain an extract C; then, the obtained extract C is put on a machine for GC-MS testing, and the extract C is quantitatively analyzed to test the residual amount W of the coating agent at this time. t ;

[0062] The pre-reaction degree DR of the coating agent is calculated according to the following formula:

[0063] DR=1-W t / (k×W0);

[0064] in,

[0065] DR: degree of pre-reaction of coating agent, unit: %;

[0066] k: coating agent reaction coefficient, 0.02;

[0067] W0: mass content of added coating agent, unit %;

[0068] W t : The residual amount of coating agent when the reaction reaches a certain extent, unit: ppm.

[0069] The present invention provides a method for evaluating the coating effect of a coated modified filler powder for a thermal interface. As described above, the present invention conducts multi-directional coordinated and refined testing and characterization of the microscopic interface structure of the coated modified filler powder for thermal interface materials, and establishes an evaluation method for the coating effect of the coated modified filler powder for a thermal interface, which can be used to predict the quality of the surface coating effect of the filler powder, that is, it is not necessary to mix the coated filler powder into the final product formula, but only by testing the coated powder, it is possible to effectively and accurately predict the performance after mixing into the formula, without formula verification, short test cycle, low raw material consumption, and can intuitively characterize each powder. In addition, the method of the present invention also has the function of guiding the control of the interface layer of the powder and achieving high-precision coating of the powder, guiding formula development. DETAILED DESCRIPTION

[0070] The present invention provides a method for evaluating the coating effect of a coated modified filler powder for a thermal interface, comprising the following steps:

[0071] Analyze and characterize the coated modified filler powder for thermal interface;

[0072] The coated modified filler powder is obtained by coating and modifying the filler powder with a coating agent;

[0073] The analytical characterization includes:

[0074] Project (1): Test the residual rate of coating agent for coated modified filler powder;

[0075] Project (2): Test the effective grafting density of coated modified filler powder;

[0076] Project (3): Test the change rate of specific surface area of ​​filler powder before and after coating;

[0077] Project (4): Test the particle size change rate of filler powder before and after coating;

[0078] Project (5): Testing the surface energy of coated modified filler powder;

[0079] There is no order restriction for the above test items (1) to (5).

[0080] In the present invention, the relevant terms are explained as follows: gas chromatography-mass spectrometry test method (GC-MS), thermogravimetric test method (TGA), laser particle size distribution test method (LPSD), specific surface area test method (BET), surface energy test method (SE).

[0081] About project (1): Testing the residual rate of coating agent for coated modified filler powder:

[0082] In the present invention, the residual rate of the unreacted coating agent on the coated modified filler powder is analyzed and tested by the GC-MS testing method.

[0083] In the present invention, the testing process of the above item (1) preferably specifically includes: using the GC-MS testing method and the external standard method to quantitatively analyze the coated modified filler powder sample, so as to obtain the coating agent residual rate in the coated modified filler powder sample.

[0084] In the present invention, the method of quantitative analysis by external standard method in the above-mentioned item (1) is not particularly limited, and can be performed according to the operation of conventional external standard method, specifically comprising: S1, establishing an external standard curve; S2, performing GC-MS test on the test solution of the coated modified filler powder sample to obtain the GC-MS test value of the test solution of the coated modified filler powder sample; S3, matching the GC-MS test value of the test solution of the coated modified filler powder sample with the external standard curve to obtain the coating agent content in the coated modified filler powder sample.

[0085] About step S1: The process of establishing an external standard curve in step S1 preferably includes: first mixing the coating agent with the solvent to prepare a series of standard products with different concentrations; then, performing GC-MS test on the series of standard products with different concentrations to obtain a series of GC-MS test values ​​(i.e., GC-MS test peak area); using a series of different concentrations of the standard product as the horizontal coordinate and a corresponding series of GC-MS test values ​​as the vertical coordinate to establish a standard curve, i.e., an external standard curve. Wherein, the solvent is preferably at least one of dichloromethane, acetone, tetrahydrofuran, n-pentane, acetonitrile and n-hexane. The concentration range of the series of different concentrations is preferably 5 to 20000 ppm. The present invention preferably establishes a standard curve with 5 to 1000 ppm and a standard curve with 1000 to 20000 ppm, and selects a suitable standard curve for corresponding calculation according to the test data of the test solution to be tested.

[0086] Regarding step S2: the coated modified filler powder sample test solution is preferably prepared by the following method: the coated modified filler powder sample is mixed with an extraction reagent, and ultrasonic extraction, immersion extraction, stirring extraction or high-temperature boiling is performed to obtain a clear liquid, which is the coated modified filler powder sample test solution. Among them, the extraction reagent is preferably at least one of dichloromethane, acetone, tetrahydrofuran, n-pentane, acetonitrile and n-hexane. The mass percentage of the mixed solution obtained by mixing the coated modified filler powder sample: the coated modified filler powder sample and the extraction reagent is preferably 10% to 30%, specifically 10%, 15%, 20%, 25%, 30%. The extraction time is preferably 5 to 40 minutes, specifically 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes. After extraction, take the clear liquid, that is, the coated modified filler powder sample test solution. In the present invention, after obtaining the coated modified filler powder sample test solution, GC-MS test is performed on a machine to obtain the GC-MS test value (i.e. GC-MS test peak area) of the coated modified filler powder sample test solution.

[0087] Regarding step S3: the GC-MS test value of the coated modified filler powder sample obtained in step S2 is matched with the external standard curve of step S2, so as to reversely calculate the coating agent content in the coated modified filler powder sample, that is, the coating agent residual rate (ppm) in the coated modified filler powder sample.

[0088] In the present invention, the solvent used in preparing the standard in step S1 and the extraction reagent used in extracting the clear solution in step S2 are preferably the same.

[0089] In the present invention, the process of establishing the standard curve in the above step S1 and the test of the coated modified filler powder sample in step S2 both involve GC-MS testing. In the present invention, the test conditions of the GC-MS test are preferably as follows: using an HP-5MS chromatographic column, setting a GC-MS test program, the heating program is from 100°C to 200-300°C at a rate of 5-15°C / min, and the flow rate is 1.0-2.0mL / min. Among them, the heating rate can be specifically 5°C / min, 10°C / min, 15°C / min. The target temperature can be specifically 200°C, 220°C, 240°C, 260°C, 280°C, 300°C. The flow rate can be specifically 1.0mL / min, 1.2mL / min, 1.5mL / min, 2.0mL / min.

[0090] About Project (2): Testing the effective grafting density of coated modified filler powder :

[0091] In the present invention, the total weight loss of the coated modified filler powder in the temperature range of 250 to 800° C. is measured and calculated by the TGA test method, and then the effective graft density GD of the coated modified filler powder is calculated by the following formula:

[0092]

[0093] in,

[0094] GD: effective grafting density of coated modified filler powder, unit: mmol / g;

[0095] M w : Molecular mass of the coating agent, unit: g / mol;

[0096] △m: total weight loss of coated modified filler powder in the temperature range of 250-800℃, unit: %;

[0097] 1-△m: The mass fraction of powder before coating to the total powder after coating, unit: %.

[0098] In the present invention, the test conditions of the TGA test method are preferably: nitrogen atmosphere, gas flow rate 15-60mL / min, and heating rate from room temperature to 800°C at a heating rate of 3-5°C / min. Among them, gas flow rate and heating rate are the key in this test project. Different gas flow rates result in different thermal reactions during the test, resulting in different test results. In the present invention, for gas flow rate, if the coating agent in the coated modified filler powder is different, the controlled gas flow rate is different. For example, for siloxane coating agents, the controlled gas flow rate is 15-40mL / min, specifically 15mL / min, 20mL / min, 25mL / min, 30mL / min, 35mL / min, 40mL / min; for titanate and zirconate coating agents, the controlled gas flow rate is 40-60mL / min, specifically 40mL / min, 45mL / min, 50mL / min, 55mL / min, 60mL / min. The above-mentioned heating rate can be specifically 3°C / min, 4°C / min, and 5°C / min. In the present invention, different coating agents have different test temperature ranges. For example, for siloxane coating agents, the temperature range is preferably controlled to be 500-800°C; for titanate and zirconate coating agents, the temperature range is preferably controlled to be 300-600°C. After the total weight loss △m of the coated modified filler powder in a certain temperature range is tested by the above-mentioned TGA test method, the effective grafting density GD of the coated modified filler powder can be calculated by the above formula.

[0099] About Project (3): Testing the change rate of specific surface area of ​​filler powder before and after coating :

[0100] In the present invention, the BET specific surface area is measured by the static volumetric method. Specifically, the specific surface area SA of the filler powder before coating is measured by the static volumetric method. b and the specific surface area SA of the coated modified filler powder obtained after coating a , and then calculate the specific surface area change rate SARC before and after the filler powder is coated according to the following formula:

[0101]

[0102] in,

[0103] SARC: the specific surface area change rate of filler powder before and after coating, unit: %;

[0104] SA b : Specific surface area of ​​filler powder before coating, unit: m 2 / g;

[0105] SA a : Specific surface area of ​​the coated modified filler powder obtained after coating, unit: m 2 / g.

[0106] In the present invention, both the filler powder before coating and the coated modified filler powder obtained after coating can be optionally pretreated before the specific surface area test, wherein optional means that pretreatment may be performed or not; the present invention more preferably performs pretreatment, that is, the filler powder before coating measured is the pretreated filler powder before coating, and the coated modified filler powder measured is also the pretreated coated modified filler powder.

[0107] In the present invention, the pretreatment is a heat treatment. In the present invention, the temperature and time of the pretreatment are the key to the test of this project. If the temperature is too high, the coating agent will decompose, and if the temperature is too low, the moisture cannot be effectively removed. In the present invention, the temperature of the pretreatment is preferably 120-200°C, specifically 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 180°C, 200°C. For coated modified filler powders, different coating agents have different pretreatment temperatures, as follows: for low molecular weight (relative molecular mass <200g / mol) silane coating agents, no pretreatment is performed; for high molecular weight (relative molecular mass ≥200g / mol) silane coating agents, the pretreatment temperature is preferably controlled at 120±10°C; for titanate coating agents, the pretreatment temperature is preferably controlled at 130±10°C; for zirconate coating agents, the pretreatment temperature is preferably controlled at 150±10°C. In the present invention, the pretreatment time is preferably 1 to 2 hours, specifically 1 hour, 1.5 hours, or 2 hours. After the pretreatment, the specific surface area test is performed.

[0108] In the present invention, the same pretreatment system and pretreatment conditions are preferably used for the filler powder before coating and the coated modified filler powder obtained after coating. For example, for low molecular weight silane coating agents, if the coated modified filler powder is not pretreated, then the corresponding filler powder before coating is also not pretreated. For high molecular weight silane coating agents, if the pretreatment conditions of the coated modified filler powder are: temperature 120°C, time 1h, then the corresponding filler powder before coating is also pretreated under the same conditions as above. Other powders are similar.

[0109] In the present invention, when conducting the test of the above item (3), when weighing the sample, it is preferably weighed according to the following system: if the sample particle size is less than 0.1μm, the sample weighing amount is more than 1g; if 0.1μm≤sample particle size<1μm, the sample weighing amount is more than 2g; if 1μm≤sample particle size<2μm, the sample weighing amount is more than 3g; if 2μm≤sample particle size<5μm, the sample weighing amount is 15g; if the sample particle size is greater than 5μm, the sample weighing amount is more than 20g.

[0110] About Project (4): Testing the particle size change rate of filler powder before and after coating :

[0111] In the present invention, the LPSD test method is used to test the median diameter D of the filler powder before coating. 50b The median diameter D of the coated modified filler powder obtained after coating 50a ; Then calculate the median diameter change rate RD before and after powder coating according to the following formula: 50 :

[0112]

[0113] in,

[0114] RD 50 : Median diameter D before and after powder coating 50 Rate of change, unit: %;

[0115] D 50b : Median diameter D of filler powder before coating 50 ;

[0116] D 50a : The median diameter D of the coated modified filler powder obtained after coating 50 .

[0117] In the present invention, whether for the filler powder before coating or the coated modified filler powder obtained after coating, the process of testing the particle size using the LPSD test method is preferably as follows: K1, dispersing the powder sample in a dispersion medium to obtain a dispersion; K2, transferring the dispersion into an LPSD analyzer, setting the test level, and performing a particle size test.

[0118] Regarding step K1: the dispersion medium preferably includes: a solute and a solvent. Among them, the solute is preferably sodium hexametaphosphate or a surfactant. The solvent is preferably water or ethanol. The mass fraction of the dispersion medium is preferably 5% to 20%, specifically 5%, 10%, 15%, 20%. In some embodiments of the present invention, a sodium hexametaphosphate aqueous solution with a mass fraction of 10% is used as the dispersion medium. In the present invention, the mass percentage of the powder sample in the dispersion is preferably 10% to 40%, specifically 10%, 15%, 20%, 25%, 30%, 35%, 40%.

[0119] Regarding step K2: the test program is preferably set as follows: set the ultrasonic cycle speed to 500-2500 r / min, the test time to 2-5 min, select the real and imaginary parts of the refractive index of the test substance and the refractive index of the test medium, the upper limit of the refractive index is 20%-30%, the lower limit of the refractive index is 5%-7%, and the amount of the dispersion to be tested is to make the refractive index reach 10%-20%. After setting the test program, perform LPSD test to obtain the particle size of the powder sample.

[0120] In the present invention, when performing LPSD test on the filler powder before coating and the coated modified filler powder after coating, the system and process conditions adopted are preferably consistent.

[0121] In the present invention, in addition to testing and calculating the median diameter change rate RD before and after the powder coating 50 In addition, it is preferred to test and calculate the maximum particle size change rate RD before and after the powder is coated 100 The test calculation process is preferably based on the median diameter change rate RD 50 The test calculation process is consistent with that of the previous test, namely, the LPSD test method is used to test the maximum particle size D of the filler powder before coating. 100b The maximum particle size D of the coated filler powder obtained after coating 100a ; Then calculate the maximum particle size change rate RD before and after powder coating according to the following formula: 100 :

[0122]

[0123] in,

[0124] RD 100 : Maximum particle size D before and after powder coating 100 Rate of change, unit: %;

[0125] D 100b : Maximum particle size D of filler powder before coating 100 ;

[0126] D 100a : The maximum particle size D of the coated modified filler powder obtained after coating100 .

[0127] In the present invention, the maximum particle size change rate RD is calculated by testing 100 In the process, the testing process of the maximum particle size of the sample powder is consistent with the process of testing the median particle size in the previous article, and will not be repeated here.

[0128] About Project (5): Testing the surface energy of coated modified filler powder :

[0129] In the present invention, the surface energy of the coated modified filler powder is measured and calculated by the contact angle method. In the prior art, the contact angle method involves different measurement and calculation methods, such as the Fowkes method, the Owens method, the Wu S method, and the LW-AB method. The present invention adopts the Wu S method. Specifically, it includes: H1, testing the contact angle of the coated modified filler powder; H2, calculating the surface energy of the coated modified filler powder by the calculation equation of the Wu S method.

[0130] In the present invention, the calculation equation of Wu S method is as follows:

[0131]

[0132] Where θ is the wetting contact angle between liquid and solid; γ lg is the liquid-gas interfacial tension; γ sg is the solid-gas interfacial tension; d is the dispersion force component in the interfacial tension, and p is the polar force component in the interfacial tension. The above equation contains two variables, and it is necessary to test the contact angle of the same solid interface twice with different liquids, and solve the simultaneous equations to obtain the dispersion force and polar force of the solid-gas interface, thereby obtaining the surface free energy of the solid. In the present invention, in the process of testing the contact angle twice, the titrants selected are water and diiodomethane respectively.

[0133] In the present invention, the process of testing the contact angle is preferably as follows: using the sessile drop method of a video optical contact angle meter, the coated modified filler powder sample to be tested is spread flat in the sample pool, a titrant is selected and tested with a superhydrophobic titration needle, and the contact angle θ when the titrant is dripped for a certain period of time is read. Among them, the amount of the coated modified filler powder sample to be tested is preferably 5 to 10g, specifically 5g, 6g, 7g, 8g, 9g, 10g. The titration time is preferably 2 to 5s, specifically 2s, 3s, 4s, 5s. As described above, it is necessary to perform two contact angle tests, and the selected titrants are water and diiodomethane, respectively. After obtaining different contact angles θ through two tests, the simultaneous equations are solved by the calculation equation of the Wu S method above, and finally the surface energy (mJ / m 2 ).

[0134] In the present invention, in addition to the above test items (1) to (5), it is preferred to further test item (6): analyzing the pre-reaction degree of the coating agent.

[0135] About Project (6): Analysis of the pre-reaction degree of the coating agent :

[0136] In the present invention, the pre-reaction degree of the coating agent is analyzed by a GC-MS test method. Preferably, the method specifically includes: mixing the coating agent with an alcohol aqueous solution to obtain a mixed solution A, recording the mass percentage content W0 of the coating agent in the mixed solution A; stirring the mixed solution A to react to a certain degree to obtain a reaction solution B; weighing the reaction solution B and fixing the volume with a constant volume reagent; then, ultrasonic extraction, immersion extraction, stirring extraction or high-temperature boiling; then drying to obtain an extract C; then, the obtained extract C is put on a machine for GC-MS testing, and the extract C is quantitatively analyzed to test the residual amount W of the coating agent at this time. t ;

[0137] The pre-reaction degree DR of the coating agent is calculated according to the following formula:

[0138] DR=1-W t / (k×W0);

[0139] in,

[0140] DR: degree of pre-reaction of coating agent, unit: %;

[0141] k: coating agent reaction coefficient, 0.02;

[0142] W0: mass content of added coating agent, unit %;

[0143] W t : The residual amount of coating agent when the reaction reaches a certain extent, unit: ppm.

[0144] in:

[0145] The alcohol aqueous solution is a mixture of alcohol and deionized water. The alcohol is preferably isopropanol or ethanol. The mass percentage of alcohol in the alcohol aqueous solution is preferably 1% to 20%, specifically 1%, 5%, 10%, 15%, 20%.

[0146] In the mixed solution A obtained by mixing the coating agent with the alcohol aqueous solution, the mass percentage W0 of the coating agent is preferably 2% to 5%, specifically 2%, 3%, 4%, or 5%.

[0147] The temperature for stirring the mixed solution A is preferably room temperature to 150°C, specifically 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C. The stirring reaction time is preferably 0.5h to 4h; specifically, when coating powders with a particle size of less than 1μm, the coating agent pre-reaction stirring time is 0.5h to 2h, and when coating powders with a particle size of more than 1μm, the coating agent pre-reaction stirring time is 2h to 4h. After stirring the reaction, the reaction solution B is obtained.

[0148] After obtaining the reaction solution B, the present invention weighs the reaction solution B and fixes the volume with a constant volume reagent. Among them, the weighed amount of the reaction solution B is preferably 0.1g, preferably accurate to 4 decimal places. The constant volume reagent is preferably dichloromethane, acetone, tetrahydrofuran, n-pentane, acetonitrile or n-hexane. The constant volume is preferably fixed to 5mL. After constant volume, ultrasonic extraction, immersion extraction, stirring extraction or high-temperature boiling is performed. The extraction time is preferably 10 to 20 minutes, specifically 10 minutes, 15 minutes, and 20 minutes. After extraction, drying is performed. The drying method is preferably to add anhydrous sodium sulfate for drying. After drying, extract C is obtained.

[0149] After obtaining the extract C, the extract C is put on a GC-MS machine for quantitative analysis to test the residual amount of the coating agent W at this time. t .

[0150] In the present invention, the test conditions of the GC-MS test are preferably as follows: using an HP-5MS chromatographic column, setting a GC-MS test program, the temperature rise program is from 100°C to 200-300°C at a rate of 5-15°C / min, and the flow rate is 1.0-4.0mL / min. Among them, the temperature rise rate can be specifically 5°C / min, 10°C / min, 15°C / min. The target temperature can be specifically 200°C, 220°C, 240°C, 260°C, 280°C, 300°C. The flow rate can be specifically 1.0mL / min, 1.5mL / min, 2.0mL / min, 2.5mL / min, 3.0mL / min, 3.5mL / min, 4.0mL / min.

[0151] The present invention analyzes the pre-reaction degree of the coating agent through item (6) to determine whether the coating agent is usable. Only powder coated with a coating agent with a suitable treatment degree can meet the use requirements.

[0152] In the present invention, the order of the analysis and testing of the above items (1) to (6) is not particularly limited.

[0153] In the present invention, most of the test objects in the above-mentioned analysis and test items are coated modified filler powders, that is, the filler powders are coated and modified by using a coating agent. The present invention has no special restrictions on the type of the coated modified filler powders, and it can be a conventional coated modified powder in the art. Among them, the filler powder is preferably at least one of aluminum nitride powder, aluminum oxide powder, magnesium oxide powder, boron nitride powder, silicon carbide powder, aluminum powder, zinc oxide powder, aluminum hydroxide powder and silicon micropowder. The coating agent is preferably at least one of a coupling agent and a coupling agent oligomer; wherein, the coupling agent is preferably at least one of a silane coupling agent, a titanate coupling agent, a zirconate coupling agent and an aluminate coupling agent. The type of coupling agent in the coupling agent oligomer is the same as above. In individual embodiments of the present invention, the filler powder is aluminum nitride powder, and the coating agent is n-dodecyltrimethoxysilane coupling agent.

[0154] In a particular embodiment of the present invention, in addition to the above-mentioned analysis and characterization of the coated modified filler powder for thermal interface, the following steps are further performed: the obtained analysis and characterization results are judged: when the analysis and characterization results of items (1) to (5) simultaneously reach the following levels, the coated modified filler powder is judged to be qualified;

[0155] Item (1): The residual rate of coating agent in the coated modified filler powder sample is less than 500 ppm;

[0156] Item (2): The effective grafting density GD of the coated modified filler powder is 0.03-0.1 mmol / g;

[0157] Item (3): The specific surface area change rate SARC of the filler powder before and after coating is 0% to 10%;

[0158] Item (4): Change rate of median diameter RD of filler powder before and after coating 50 0%~200%;

[0159] Item (5): The surface energy of the coated modified filler powder is 20-30 mJ / m 2 .

[0160] In the present invention, judging whether the coated modified filler powder is qualified refers to predicting whether the coated modified filler powder is qualified in practical applications, and more specifically, whether the coated modified powder is qualified in terms of formula flow rate and reliability in practical applications, that is, if the various index evaluation standards of step b) are met, it can be predicted that the coated modified powder is qualified in at least two aspects of formula flow rate and reliability in practical applications, and if the various index evaluation standards of step b) are not met, it can be predicted that the coated modified powder is unqualified in at least two aspects of formula flow rate and reliability in practical applications. Among them, in practical applications, the higher the flow rate, the better. In individual embodiments of the present invention, the flow rate is judged to be qualified when it is ≥20g / min; the reliability test is to test the modulus change rate of the sample formula after aging at 150°C for 1000 times. Generally, if the modulus change rate is <15%, it is judged to be qualified.

[0161] At present, the existing evaluation methods for the effect of thermal conductive filler coating in the industry are mostly focused on the comprehensive verification of formula performance, such as the characterization of thermal conductivity, fluidity, stability, etc. These are all indirect methods for characterizing the coating effect of powders. Such evaluation methods not only have a long test cycle, but also high raw material consumption. At the same time, the industry lacks effective and accurate evaluation methods for testing the coated modified filler powder itself to predict the effect after mixing it into the formula. The existing prediction methods include surface wettability, activation index, oil absorption value, dispersibility viscosity method (testing the viscosity in the formula), etc., but these evaluation methods are low in accuracy and effectiveness. They are rough evaluation methods. For example, different samples have similar or basically the same oil absorption value, activation index, viscosity and other characteristics, but in actual use, some samples can pass the test while others cannot, so it is impossible to accurately and effectively evaluate the effect of powder coating modification. Therefore, most of the current scientific research and production methods adopt the method of directly mixing the coated modified filler powder into the final product formula for actual application, and then evaluating the coating modification effect based on the actual application effect. However, there is a lack of effective and accurate evaluation methods for testing the coated modified filler powder itself to predict the effect after mixing into the formula. In other words, the effect can only be judged after the formula is actually made and used, and no prediction can be made. The reason for the lack of accurate and effective prediction evaluation methods is the lack of accurate characterization of the powder coating structure, the inability to accurately characterize and evaluate the differences in the microscopic interface structure of the powder coating, the inability to establish the corresponding relationship between the microstructure and the performance effect, and thus the inability to accurately and effectively evaluate the effect of the powder coating modification.

[0162] The present invention provides a method for evaluating the coating effect of a coated modified filler powder for a thermal interface. As described above, the present invention conducts multi-directional coordinated and refined testing and characterization of the microscopic interface structure of the coated modified filler powder for thermal interface materials, and establishes an evaluation method for the coating effect of the coated modified filler powder for a thermal interface, which can be used to predict the quality of the surface coating effect of the filler powder, that is, it is not necessary to mix the filler powder into the final product formula, but only by testing the coated powder, it is possible to effectively and accurately predict the performance after mixing into the formula, without formula verification, short test cycle, low raw material consumption, and can intuitively characterize each powder. In addition, the method of the present invention also has the function of guiding the control of the interface layer of the powder and achieving high-precision coating of the powder, guiding formula development.

[0163] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0164] Preparatory example: Preparation of coated modified filler powder

[0165] Sample a:

[0166] To aluminum nitride powder (D 50 n-Dodecyltrimethoxysilane coupling agent (the amount of coupling agent is 1% of the mass of the powder) was added into the prepared granular material (with a particle size of 1 μm), and the mixture was stirred at 100° C. for 2 h. During stirring, the maximum movement speed was controlled to be 10 m / s to obtain a coated modified filler powder (referred to as sample a).

[0167] Sample b:

[0168] To aluminum nitride powder (D 50 n-Dodecyltrimethoxysilane coupling agent (the amount of coupling agent is 1% of the mass of the powder) was added into the prepared granular material (with a particle size of 1 μm), and the mixture was stirred at 100° C. for 2 h. During stirring, the maximum movement speed was controlled to be 5 m / s to obtain a coated modified filler powder (referred to as sample b).

[0169] Sample c:

[0170] To aluminum nitride powder (D 50 n-Dodecyltrimethoxysilane coupling agent (the amount of coupling agent is 2% of the mass of the powder) was added into the prepared granular material (with a particle size of 1 μm), and the mixture was stirred at 100° C. for 2 h. During stirring, the maximum movement speed was controlled to be 10 m / s to obtain a coated modified filler powder (referred to as sample c).

[0171] Comparative Example 1: Existing evaluation method

[0172] 1. Sample evaluation

[0173] The oil absorption value, activation index and viscosity of samples a to c were tested. The results are shown in Table 1.

[0174] The viscosity test method is the dispersion viscosity method to test the viscosity in the formula. Specifically, the formula preparation process is as follows: 30g of the coated modified filler powder and 10g of dimethyl silicone oil (viscosity 200cp) are mixed and stirred evenly to obtain a formula sample.

[0175] Table 1: Test results of existing evaluation methods

[0176] Oil absorption value (mg / 100g) Activation index (%) Formula viscosity (cp) Sample a 15 50 20000 Sample b 15 50 20000 Sample c 15 50 20000

[0177] 2. Actual application effect

[0178] 2.1. Sample preparation formula

[0179] 30 g of the coated modified filler powder and 10 g of dimethyl silicone oil (viscosity 200 cp) were mixed and stirred uniformly to obtain a formula sample.

[0180] 2.2. Practical application effect test of sample formula

[0181] The flow rate and reliability of the above sample formula were tested, where the higher the flow rate, the better. Generally, the flow rate ≥ 20g / min (30cc EFD hose @ 60psi) is considered qualified; the reliability test is to test the modulus change rate of the sample formula after aging at 150℃ for 1000 hours. Generally, if the modulus change rate is <15%, it is considered qualified. See Table 2 for the actual application test results.

[0182] Table 2: Practical application effects of samples a to c

[0183] Actual formula flow rate (g / min) reliability(%) Comprehensive practical application effect Sample a 30(passed) 10(passed) qualified Sample b 10 (Unqualified) 20 (failed) Failure Sample c 50(passed) 100 (failed) Failure

[0184] It can be seen from the test results in Table 1 that the oil absorption value, activation index and viscosity of sample a, sample b and sample c are the same, and it is impossible to distinguish between sample a, sample b and sample c. However, it can be seen from the test results in Table 2 that the effects of sample a, sample b and sample c in actual application are different, among which sample a is qualified and sample bc is not qualified. It can be seen that the existing evaluation method of comparative example 1 cannot effectively predict the actual application effect of the coated modified filler powder after it is mixed into the final product formula.

[0185] Example 1: Evaluation method of the present invention

[0186] 1. Sample evaluation

[0187] a) Analyze and characterize the coated modified filler powder for thermal interface:

[0188] Project (1): Test the residual rate of coating agent for coated modified filler powder:

[0189] The GC-MS test method was used to analyze the residual rate of the unreacted coating agent on the coated modified filler powder, as follows:

[0190] S1. Establish external standard curve:

[0191] First, the coating agent (n-dodecyl trimethoxy silane coupling agent) and the solvent (dichloromethane) are mixed to prepare a series of standard products with different concentrations; then, the series of standard products with different concentrations are subjected to GC-MS test to obtain a series of GC-MS test values ​​(i.e., GC-MS test peak areas); a standard curve, i.e., an external standard curve, is established with a series of different concentrations of the standard product as the horizontal coordinate and a corresponding series of GC-MS test values ​​as the vertical coordinate. Among them, a standard curve is established with 5 to 1000 ppm, and a standard curve is established with 1000 to 20000 ppm, and a suitable standard curve is selected according to the test data of the test solution to be tested for corresponding calculation.

[0192] The conditions of the GC-MS test are as follows: using an HP-5MS chromatographic column, setting a GC-MS test program, and heating the temperature from 100°C to 300°C at a rate of 10°C / min, keeping the temperature for 5 minutes, and a flow rate of 1.2 mL / min.

[0193] S2. Test solution for coated modified filler powder sample

[0194] The coated modified filler powder sample is mixed with the extraction reagent (dichloromethane), and the mass percentage of the obtained mixed solution is 20%, and then the mixture is soaked and extracted for 10 minutes, and the clear liquid is taken, that is, the coated modified filler powder sample test solution. The test solution is put on the machine for GC-MS test, so as to obtain the GC-MS test value (i.e., GC-MS test peak area) of the coated modified filler powder sample test solution.

[0195] The conditions of the GC-MS test are as follows: HP-5MS chromatographic column is used, and the GC-MS test program is set. The temperature program is to increase the temperature from 100°C to 300°C at a rate of 10°C / min, keep warm for 5 minutes, and the flow rate is 1.2mL / min.

[0196] S3. Calculate the residual rate of coating agent

[0197] The GC-MS test value of the coated modified filler powder sample obtained in step S2 is matched with the external standard curve of step S2, so as to reversely calculate the coating agent content in the coated modified filler powder sample, that is, the coating agent residual rate (ppm) in the coated modified filler powder sample.

[0198] Project (2): Test the effective grafting density of coated modified filler powder:

[0199] The total weight loss of the coated modified filler powder in the temperature range of 250-800°C was measured and calculated by the TGA test method, and then the effective grafting density GD of the coated modified filler powder was calculated by the following formula:

[0200]

[0201] in,

[0202] GD: effective grafting density of coated modified filler powder, unit: mmol / g;

[0203] M w : Molecular mass of the coating agent, unit: g / mol;

[0204] △m: total weight loss of coated modified filler powder in the temperature range of 250-800℃, unit: %;

[0205] 1-△m: The mass fraction of powder before coating to the total powder after coating, unit: %.

[0206] The test conditions of the TGA test method are: nitrogen atmosphere, gas flow rate 20 mL / min, and heating rate from room temperature to 800°C at 5°C / min.

[0207] Project (3): Test the change rate of specific surface area of ​​filler powder before and after coating:

[0208] The filler powder before coating and the coated modified filler powder after coating were first pretreated at a temperature of 120°C for 1 hour. Then, the BET specific surface area was measured by the static volumetric method. Specifically, the specific surface area SA of the filler powder before coating was measured by the static volumetric method. b and the specific surface area SA of the coated modified filler powder obtained after coating a , and then calculate the specific surface area change rate SARC before and after the filler powder is coated according to the following formula:

[0209]

[0210] in,

[0211] SARC: the specific surface area change rate of filler powder before and after coating, unit: %;

[0212] SA b : Specific surface area of ​​filler powder before coating, unit: m 2 / g;

[0213] SA a : Specific surface area of ​​the coated modified filler powder obtained after coating, unit: m 2 / g.

[0214] Project (4): Test the particle size change rate of filler powder before and after coating:

[0215] K1. Dispersing the powder sample in a dispersion medium (a sodium hexametaphosphate aqueous solution with a mass concentration of 10%) to obtain a dispersion liquid (the mass percentage of the powder sample in the dispersion liquid is 16%);

[0216] K2. Move the dispersion into the LPSD analyzer, set the test level, and perform a particle size test. The test program is preferably set as follows: set the ultrasonic cycle speed to 1600 r / min, the test time to 3 min, select the refractive index of the test substance to be 2.01 for the real part and 0.1 for the imaginary part, the refractive index of the test medium to be 1.33, the upper limit of the refractive index to be 20%, the lower limit of the refractive index to be 5%, and the amount of the dispersion to be tested to make the refractive index reach 10% to 15%.

[0217] According to the above method, the median diameter D of the filler powder before coating was measured. 50b The median diameter D of the coated modified filler powder obtained after coating 50a ; Then calculate the median diameter change rate RD before and after powder coating according to the following formula: 50 :

[0218]

[0219] in,

[0220] RD 50 : Median diameter D before and after powder coating 50 Rate of change, unit: %;

[0221] D 50b : Median diameter D of filler powder before coating 50 ;

[0222] D 50a : The median diameter D of the coated modified filler powder obtained after coating 50 .

[0223] Project (5): Testing the surface energy of coated modified filler powder:

[0224] H1. Test the contact angle of the coated modified filler powder; specifically, use the sessile drop method of the video optical contact angle measuring instrument, spread 7g of the coated modified filler powder sample in the sample pool, select a titrant and use a superhydrophobic titration needle for testing, and read the contact angle θ when the titrant is dripped for 2s. Perform two contact angle tests, and select water and diiodomethane as titrants in the two tests respectively.

[0225] H2. The surface energy of the coated modified filler powder is calculated by the calculation equation of the Wu S method. Specifically, the calculation equation of the Wu S method is as follows:

[0226]

[0227] Where θ is the wetting contact angle between liquid and solid; γ lg is the liquid-gas interfacial tension; γ sg is the solid-gas interfacial tension; d is the dispersion force component of the interfacial tension, and p is the polar force component of the interfacial tension. The above equation contains two variables. Two different liquids are used to test the same solid interface. The dispersion force and polar force of the solid-gas interface are obtained by solving the simultaneous equations, thereby obtaining the surface free energy of the solid.

[0228] b) Judging the analytical characterization results obtained in step a): When the analytical characterization results of items (1) to (5) simultaneously reach the index levels mentioned above, the coated modified filler powder is judged to be qualified. The judgment results of samples a to c are shown in Table 3.

[0229] Table 3: Judgment results of the evaluation method of the present invention

[0230]

[0231] 2. Actual application effect

[0232] See Section 2 of Comparative Example 1 above, and the actual application test results are shown in Table 2 above, as follows:

[0233] Table 2: Practical application effects of samples a to c

[0234] Actual formula flow rate (g / min) reliability(%) Comprehensive practical application effect Sample a 30(passed) 10(passed) qualified Sample b 10 (Unqualified) 20 (failed) Failure Sample c 50(passed) 100 (failed) Failure

[0235] As can be seen from Table 3, the evaluation method of the present invention can distinguish sample a, sample b and sample c, can accurately characterize the coating effect, and can predict whether the sample is qualified through the evaluation criteria of step b). Combined with the effects of Table 2 in actual application, the actual application effects of samples ac are consistent with the prediction results of Table 3 in the method of the present invention. Therefore, the evaluation method of the present invention can effectively and accurately predict the actual application effect of the coated modified filler powder after mixing into the final product formula.

[0236] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A method for evaluating the coating effect of a coated modified filler powder for a thermal interface, characterized in that: The following steps are involved: Analyze and characterize the coated modified filler powder for thermal interface; The coated modified filler powder is obtained by coating and modifying the filler powder with a coating agent; The coating agent is at least one of a coupling agent and a coupling agent oligomer; wherein the coupling agent is at least one of a silane coupling agent, a titanate coupling agent and a zirconate coupling agent; the coupling agent oligomer is at least one of a silane coupling agent oligomer, a titanate coupling agent oligomer and a zirconate coupling agent oligomer; The analytical characterization includes: Item (1): testing the residual rate of the coating agent of the coated modified filler powder; Item (1) specifically comprises: S1, establishing an external standard curve; S2, performing GC-MS test on the coated modified filler powder sample test solution to obtain the GC-MS test value of the coated modified filler powder sample test solution; S3, matching the GC-MS test value of the coated modified filler powder sample test solution with the external standard curve to obtain the coating agent content in the coated modified filler powder sample; Project (2): Testing the effective grafting density of coated modified filler powder; specifically including: The total weight loss of the coated modified filler powder in the temperature range of 250~800℃ was measured and calculated by the TGA test method, and then the effective grafting density GD of the coated modified filler powder was calculated by the following formula: ; in, GD: effective grafting density of coated modified filler powder, unit: mmol / g; M w : Molecular mass of the coating agent, unit: g / mol; △m: Total weight loss of coated modified filler powder in the temperature range of 250~800℃, unit: % The test conditions of the TGA test method are: nitrogen atmosphere, gas flow rate 15~60mL / min, heating from room temperature at a heating rate of 3~5℃ / min; Project (3): Test the specific surface area change rate (SARC) of filler powder before and after coating; Project (4): Test the particle size change rate of filler powder before and after coating, including test and calculation of the median diameter change rate RD of filler powder before and after coating 50 ; Project (5): Testing the surface energy of coated modified filler powder; There is no order restriction for the above items (1) to (5), and the obtained analytical characterization results are judged: when the analytical characterization results of items (1) to (5) simultaneously reach the following levels, the coated modified filler powder is judged to be qualified; Item (1): The residual rate of coating agent in the coated modified filler powder sample is less than 500 ppm; Item (2): The effective grafting density GD of the coated modified filler powder is 0.03~0.1mmol / g; Item (3): The specific surface area change rate SARC of the filler powder before and after coating is 0%~10%; Item (4): Change rate of median diameter RD of filler powder before and after coating 50 0%~200%; Project (5): The surface energy of the coated modified filler powder is 20~30mJ / m 2 ; Also tested was item (6): analysis of the pre-reaction degree of the coating agent; The pre-reaction degree of the coating agent is analyzed by a GC-MS test method; specifically, the coating agent is mixed with an alcohol aqueous solution to obtain a mixed solution A, and the mass percentage content W0 of the coating agent in the mixed solution A is recorded; the mixed solution A is stirred for 0.5h to 4h to obtain a reaction solution B; the reaction solution B is weighed and fixed with a volume fixing agent, and the volume fixing agent is dichloromethane, acetone or n-hexane; then, ultrasonic extraction, immersion extraction, stirring extraction or high-temperature boiling is performed; then, drying is performed to obtain an extract C; then, the obtained extract C is put on a machine for GC-MS testing, and the extract C is quantitatively analyzed to test the residual amount W of the coating agent at this time. t ; The pre-reaction degree DR of the coating agent is calculated according to the following formula: DR=1-W t / (k×W0); in, DR: coating agent pre-reaction degree, unit: %; k: coating agent reaction coefficient, 0.02; W0: mass percentage of added coating agent, unit: % W t : Residual amount of coating agent, unit: ppm.

2. The evaluation method according to claim 1, characterized in that: Project (3): Test the specific surface area change rate (SARC) of filler powder before and after coating, including: The specific surface area SA of the filler powder before coating was tested by static volumetric method. b and the specific surface area SA of the coated modified filler powder obtained after coating a , and then calculate the specific surface area change rate SARC before and after the filler powder is coated according to the following formula: ; in, SARC: Change rate of specific surface area of ​​filler powder before and after coating, unit: %; SA b : Specific surface area of ​​filler powder before coating, unit: m 2 / g; S a : Specific surface area of ​​the coated modified filler powder obtained after coating, unit: m 2 / g; In item (4): Test and calculate the median diameter change rate RD of filler powder before and after coating 50 , specifically including: The median diameter D of the filler powder before coating was measured using the LPSD test method. 50b The median diameter D of the coated modified filler powder obtained after coating 50a ; Then calculate the median diameter change rate RD of the filler powder before and after coating according to the following formula: 50 : ; in, RD 50 : Median diameter D before and after filling powder coating 50 Rate of change, unit: % D 50b : Median diameter D of filler powder before coating 50 ; D 50a : The median diameter D of the coated modified filler powder obtained after coating 50 .

3. The evaluation method according to claim 2, characterized in that: In item (3), the filler powder before coating and the coated modified filler powder obtained after coating are both pre-treated before the specific surface area test; The pretreatment is a heat treatment; the pretreatment temperature is 120-200°C and the time is 1-2h.

4. The evaluation method according to claim 2, characterized in that: In item (4), the process of testing the median diameter using the LPSD test method specifically includes: K1, dispersing the powder sample in a dispersion medium to obtain a dispersion; K2, transferring the dispersion into an LPSD analyzer, setting the test level, and performing a median diameter particle size test.

5. The evaluation method according to claim 2, characterized in that: Item (4) also includes: testing and calculating the maximum particle size change rate RD of the filler powder before and after coating 100 ; The test calculates the maximum particle size change rate RD of the filler powder before and after coating 100 The process includes: using the LPSD test method to test the maximum particle size D of the filler powder before coating 100b The maximum particle size D of the coated modified filler powder obtained after coating 100a ; Then calculate the maximum particle size change rate RD of the filler powder before and after coating according to the following formula: 100 : ; in, RD 100 : Maximum particle size D of filler powder before and after coating 100 Rate of change, unit: % D 100b : Maximum particle size D of filler powder before coating 100 ; D 100a : The maximum particle size D of the coated modified filler powder obtained after coating 100 .

6. The evaluation method according to claim 2, characterized in that: Item (5) specifically includes: The coated modified filler powder sample to be tested is spread flat in the sample pool, and a titrant is selected and a contact angle test is performed using a superhydrophobic titration needle. Two contact angle tests are required, and the titrants selected are water and diiodomethane respectively; after different contact angles are obtained through the two tests, the dispersion force and polar force of the solid-gas interface are obtained by solving the calculation equation of the Wu S method, and finally the surface energy of the coated modified filler powder is obtained; The calculation equation of the Wu S method is as follows: ; Where θ is the wetting contact angle between liquid and solid; γ lg is the liquid-gas interfacial tension; γ sg is the solid-gas interfacial tension; d is the dispersion force component in the interfacial tension, and p is the polar force component in the interfacial tension.

7. The evaluation method according to claim 6, characterized in that: In item (5): Spread 5-10 g of the coated modified filler powder sample in the sample pool, select a titrant and use a super-hydrophobic titration needle to perform a contact angle test, and read the contact angle when the titrant is dripped for 2-5 seconds.

Citation Information

Patent Citations

  • Test method of silanization reaction

    CN110865145A

  • Application of modified zinc oxide filler

    CN115260793A